Paediatric respiratory nursing posts in secondary care reduce asthma morbidity, but provision is variable. Issue 8 (17th November 2008) - McKean, M; Furness, J
Abstract : British guidelines on asthma recommend nurse delivered structured discharges for all children with asthma. This study carried out a postal and telephone survey to investigate the provision of this service. Twenty out of 34 (59%) hospitals in the Northern and Yorkshire regions do not have a recognised paediatric respiratory nurse post to facilitate this aspect of care.